Formation of Viral Ribonucleic Acid and Virus in Cells that are Permissive or Nonpermissive for Murine Encephalomyelitis Virus (GDVII) - Sturman, Lawrence S. (1969)
GDVII virus growth in BHK-21 cells, a permissive host for the virus, resembled productive infections with other picornaviruses. Virus yields ranged from 100 to 600 plaque-forming units (PFU)/cell. Virus replication in HeLa cells, a nonpermissive host for GDVII virus, was characterized by virus yields of only 0.1 to 5 PFU/cell. Similar low yields of virus have been obtained from HeLa cells at all multiplicities of input up to 6,000 per cell. The progeny particles from HeLa cells were, like the infecting particles, restricted in the HeLa cell host. Despite the great difference in final yields of virus from BHK-21 and HeLa cells, the times when maximal yields were reached were similar. GDVII virus stock grown in BHK-21 cells was designated HeLa(-). A variant of GDVII virus which is capable of extensive growth in HeLa cells was obtained. This variant, designated HeLa(+) GDVII virus, was passaged serially in HeLa cells. Virus yields of 50 to 150 infective virus particles per cell were obtained from infection of HeLa cells with HeLa(+) GDVII virus. The major species of HeLa(+) virus-specific ribonucleic acid (RNA) produced was single stranded and sedimented with an S value of 35S. The rate of accumulation of HeLa(+) virus-specific RNA in HeLa cell cultures was about four times that of HeLa(-) RNA. The amount of virus-specific HeLa(+) RNA formed in HeLa cells was several-fold greater than that of HeLa(-) RNA. With HeLa(-) parent GDVII virus undergoing productive replication in BHK-21 cells or abortive replication in HeLa cells, the major species of virus-specific RNA produced was single stranded and sedimented with an approximate S value of 35S. The amount of HeLa(-) virus-specific RNA extracted from BHK-21 cells was several-fold greater than the amount obtained from HeLa cells.